1998
DOI: 10.1097/00001756-199812010-00024
|View full text |Cite
|
Sign up to set email alerts
|

Psilocybin induces schizophrenia-like psychosis in humans via a serotonin-2 agonist action

Abstract: Psilocybin, an indoleamine hallucinogen, produces a psychosis-like syndrome in humans that resembles first episodes of schizophrenia. In healthy human volunteers, the psychotomimetic effects of psilocybin were blocked dose-dependently by the serotonin-2A antagonist ketanserin or the atypical antipsychotic risperidone, but were increased by the dopamine antagonist and typical antipsychotic haloperidol. These data are consistent with animal studies and provide the first evidence in humans that psilocybin-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
703
1
17

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 829 publications
(789 citation statements)
references
References 7 publications
30
703
1
17
Order By: Relevance
“…The constellation of symptoms produced by D-9-THC resembles several dimensions of endogenous psychotic disorders like schizophrenia. The findings of this study provide support for a cannabinoid 'model' psychosis (Beringer and Marx, 1932) just as dopaminergic (DA) stimulants (amphetamine), serotonergic agents (LSD and psylocibin), and glutamatergic antagonists (ketamine) have been studied as laboratory-based models of endogenous psychotic disorders (Adler et al, 1998;Angrist et al, 1974;Ellison, 1994;Krystal et al, 1994;Lieberman et al, 1987;Malhotra et al, 1996;Siomopoulos, 1975;Snyder, 1973;Vollenweider et al, 1998Vollenweider et al, , 2000. In contrast to DA stimulants, D-9-THC like ketamine produced positive, negative, and cognitive symptoms of psychosis.…”
Section: Discussionsupporting
confidence: 55%
“…The constellation of symptoms produced by D-9-THC resembles several dimensions of endogenous psychotic disorders like schizophrenia. The findings of this study provide support for a cannabinoid 'model' psychosis (Beringer and Marx, 1932) just as dopaminergic (DA) stimulants (amphetamine), serotonergic agents (LSD and psylocibin), and glutamatergic antagonists (ketamine) have been studied as laboratory-based models of endogenous psychotic disorders (Adler et al, 1998;Angrist et al, 1974;Ellison, 1994;Krystal et al, 1994;Lieberman et al, 1987;Malhotra et al, 1996;Siomopoulos, 1975;Snyder, 1973;Vollenweider et al, 1998Vollenweider et al, , 2000. In contrast to DA stimulants, D-9-THC like ketamine produced positive, negative, and cognitive symptoms of psychosis.…”
Section: Discussionsupporting
confidence: 55%
“…A number of functional animal studies have suggested that indoleamine (psilocybin, LSD) and phenylethylamine (DOI, mescaline) hallucinogens produce their psychotomimetic effects primarily through excessive stimulation of 5-HT, and 5-HT 2A receptors in particular (McKenna et al 1989;Pierce and Peroutka 1989;Aghajanian 1994;Sipes and Geyer 1994;Padich et al 1996). This assumption was corroborated in a recent human study demonstrating that the psychotomimetic effects of psilocybin can be blocked dose-dependently by pretreatment with the preferential 5-HT 2A receptor antagonist ketanserin (Vollenweider et al 1998). However, pretreatment with the D 2 -antagonist haloperidol also reduces some of the positive symptoms of psilocybin psychosis.…”
Section: The Modulating Effects Of Serotonin On Dopamine Neurotransmimentioning
confidence: 88%
“…However, pretreatment with the D 2 -antagonist haloperidol also reduces some of the positive symptoms of psilocybin psychosis. This raises the possibility that symptoms of psilocybin are secondary responses to increased dopaminergic transmission (Vollenweider et al 1998). Hence, a contribution of the dopamine systems to the effects of psilocybin, presumably through a serotonindopamine interaction, cannot be ruled out.…”
Section: The Modulating Effects Of Serotonin On Dopamine Neurotransmimentioning
confidence: 99%
“…Atypical antipsychotic drugs, which have superior therapeutic and side effect profiles, bind with high affinity to various subtypes of serotonin receptors, including 5-HT 2A and 5-HT 2C receptors (Roth and Meltzer 1995). In addition, hallucinogenic drugs such as lysergic acid diethylamide (LSD) and psilocybin, which produce behavioral and cerebral metabolic disturbances that resemble symptoms of acute schizophrenia (Vollenweider et al 1997(Vollenweider et al , 1998, are agonists at 5-HT 2A and 5-HT 2C receptors (Burris et al 1991;Egan et al 1998). The pharmacological properties of the 5-HT 2C receptor (5-HT 2C R) have also suggested a role in depression (Moreau et al 1996;Martin et al 1998) as well as anxiety (Kennett et al 1997).…”
mentioning
confidence: 99%